Implementation of Employee Work Ethics (Study on Baitul Maal wa al Tamwil (BMT) Maslahah Cooperation) - Syuhri, Saifuddin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam Syarifuddin Lumajang, 2025)
Competition from financial institutions such as Baitul Maal Wa Al Tamwil (BMT) cannot be avoided, so employee performance and customer satisfaction are essential in running a business. This research method is descriptive qualitative. The result is that implementing of employee work ethics is influenced by the religious, cultural, socio-political, geographical environment, education and economic structure factors. Meanwhile, the fundamental values as the basis of Islamic work ethics are: monotheism, justice (al Adl), prophethood (a Nubuwah), government (khilafah), results (ma'ad) and carrying out activities based on the principles of siddiq/honesty, tabligh/transparency, Trustworthy/responsible and fathonah/professional as well as avoiding the elements of maysir (gambling), tadlis (fraud), gharar (uncertainty), usury, zulm (persecution), risywah (bribery).